Wnt Signalling in Malignant Mesothelioma - Richards, Alexander S.K. (Curtin University, 2016)
The aims of this thesis were to characterise the Wnt signalling system and its pharmacological modulation in mesothelioma derived cell lines using monolayer and three dimensional culture models. Investigations into the effects upon expression of Wnt signal components were performed by inhibiting tankyrase enzymes with the compound XAV939 and histone deacetylase enzymes with suberoylanilide hydroxamic acid. Measurement of effects was carried out using functional assays and RNA sequencing for differential gene expression.